Characteristics of Mustafa (S.A.W.W) in Archaeology Literature of Sufis: صوفیہ کے ملفوظاتی ادب میں خصائص مصطفیٰﷺ (خصوصی مطالعہ) - Rehman, Dr. Ammara; Yaqoob, Hafiz Sajid (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
The contributions of Sufis have been universally accepted in the promotion and spread of Islam, especially in the awakening of love and obedience for the last Holy Prophet Muhammad (S.A.W.W). Moreover, they have prominent role in developing the concern for here after thereby inculcating piety and enlightening the mind and heart of the Muslims followers. In order to illuminate the hearts of Muslims with the pure spirit of Islam, these scholars not only have delivered speeches but have also struggled in written form. They ensured the chastisement of souls in every possible way. The discussion on different aspects of the life of the Holy Prophet (S.A.W.W) along with various and wide ranged debates on Tasawwuf are quite prominent in the malfuzati literature of these saints if analyzed. For they have presented the life of Holy Prophet (S.A.W.W), in front of the followers, as a perfect model to be followed. They have given special details to the beliefs regarding Holy Prophet (S.A.W.W) describing His ethics, respect and love, specialties and miracles and his rights on his ummah. This article deals with these specialties presented in malfuzati literature.